Continuous Flattening of a Regular Tetrahedron with Explicit Mappings - Jin-ichi Itoh; Chie Nara (Моделирование и анализ информационных систем)
We proved in [10] that each Platonic polyhedron P can be folded into a flat multilayered face of P by a continuous folding process of polyhedra. In this paper, we give explicit formulas of continuous functions for such a continuous flattening process in R³ for a regular tetrahedron.The article is published in the author’s wording.